2009
DOI: 10.1007/s11709-009-0033-2
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear elastic model for compacted clay concrete interface

Abstract: In this paper, a nonlinear elastic model was developed to simulate the behavior of compacted clay concrete interface (CCCI) based on the principle of transition mechanism failure (TMF). A number of simple shear tests were conducted on CCCI to demonstrate different failure mechanisms; i.e., sliding failure and deformation failure. The clay soil used in the test was collected from the "Shuang Jang Kou" earth rockfill dam project. It was found that the behavior of the interface depends on the critical water conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…From Table 3, the results also indicated that water had a significant role in determining the interface failure, where a higher degree of saturation would lower the interface shear strength. Although [16] argued that a higher degree of saturation would give higher interface shear strength of clay interface with concrete, other studies agreed with the current study's results [1][2][3]. Thus, water could be concluded to reduce the interface shear strength dominantly.…”
Section: Thin-soil Interface Soil Model Results Plotted Against Labor...supporting
confidence: 87%
“…From Table 3, the results also indicated that water had a significant role in determining the interface failure, where a higher degree of saturation would lower the interface shear strength. Although [16] argued that a higher degree of saturation would give higher interface shear strength of clay interface with concrete, other studies agreed with the current study's results [1][2][3]. Thus, water could be concluded to reduce the interface shear strength dominantly.…”
Section: Thin-soil Interface Soil Model Results Plotted Against Labor...supporting
confidence: 87%
“…Following the work of Potyondy [8], who studied the interface between soil and various construction materials, many scholars have studied the characteristics of the soil-structure interface . These studies included apparatus modifications and new test methods [9][10][11], which were used to investigate the influence of surface properties on the traditional soil-structure interface (including soil-concrete, soil-steel, and soil-cement grout interfaces) [9,[12][13][14][15][16][17][18][19][20][21][22][23][24][25]33,34], the interfaces between new materials (including ice-soil and soil-geogrid interfaces) [26][27][28][29][30][31][32], and the exterior load conditions (stress history, monotonic load, or cyclic load condition) [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Following the work of Potyondy [ 8 ], who studied the interface between soil and various construction materials, many scholars have studied the characteristics of the soil–structure interface [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. These studies included apparatus modifications and new test methods [ 9 , 10 , 11 ], which were used to investigate the influence of surface properties on the traditional soil–structure interface (including soil–concrete, soil–steel, and soil–cement grout interfaces) [ 9 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 33 , 34 ], the interfaces between new materials (including ice–soil and soil–geogrid interfaces) [ 26 , 27 , 28 ,…”
Section: Introductionmentioning
confidence: 99%